A Review on Zizyphus as Antidiabetic - Rabia Niamat, Mir Ajab Khan, Kiran Yasmin Khan, Mushtaq Ahmed, Paras Mazari, Barkat Ali, Mazhar Mustafa, Muhammad Zafar (Journal of Applied Pharmaceutical Science)
The present review paper aims to highlight the effects of extracts of genus zizyphus for the treatment of Diabetes clinically throughout the world. The basic aim is to study the hyperglycemic effect of this genus and its use. So as the effect of herbal medicine is more friendly then synthetic medicines. The effects of three species Ziziphus spinacristi, Zizyphus jojoba, and Zizyphus vulgaris have been studied clinically and have great effect on insulin secretion. While work on Zizyphus maritiana have also been done. It is concluded that genus zizyphus have potential of antidiabetic activity. Many species of Zizyphus grow widely. As natural drugs are with no or less side effects and safe for human health so they can greatly replace synthetic drugs in the forth coming future.
Keywords: Ziziphus spinacristi,Zizyphus jojoba,Zizyphus maritiana and Zizyphus vulgaris.